Anti-nationalist Europeans and pro-European nativists on the streets: visions of Europe from the left to the far right. (4th March 2022) - Caiani, Manuela; Weisskircher, Manès
ABSTRACT: For many left-wing and liberal social movement activists, support for 'Europe' and opposition to a 'nationalist' turn has become a key motivation for their activism. Paradoxically, however, their opponents at the other end of the political spectrum, far-right activists, also positively identify as European. This article analyses one of the key developments in the contemporary European protest arena, i.e. the dominance of European identities, even when activists strongly criticize real-existing European integration. First, we propose a novel conceptual framework that captures these dominant European identities. We distinguish between 'anti-nationalist Europeans' and 'pro-European nativists', underlining the existence of strong European identities across the political spectrum, deeply embedded in the mindset of activists even when they sharply criticize European integration in its current form. At the same time, these pro-European stances strongly differ in whether they are culturally inclusive or exclusive and how they relate to the question of nationalism or the nation state. Second, we apply these concepts to six key cases of movement mobilization in western Europe after the anti-austerity protests, shedding light on the anti-TTIP protests, Yanis Varoufakis' DiEM25, the anti-Brexit movement in the UK, the Sardines in Italy (including their offshoot, the Herrings in Finland), the Identitarians and PEGIDA. Third, we further contextualize the 'anti-nationalist Europeanism' and 'pro-European nativism' of these six cases, emphasizing historical roots, the facilitation of coalition building, implications for transnational practices, and the meaning of silence. Methodologically, the article draws on online and offline publications, semi-structured interviews, and survey data.